(untitled) (Research, Society and Development, 2022)
Oral squamous cell carcinoma is a common malignant lesion. ROCKs proteins are associated with pathogenesis and progression of human tumours. This study aimed to evaluate the functional role of ROCKs in the regulation of cell proliferation of oral squamous cell carcinoma in vitro. BrdU incorporation assays and KI-67 immunoexpression were performed by using SCC-4 cell line from oral squamous cell carcinoma. Control and treated cells: HA-1077 (25, 50 and 100 μmol/l), 50 μmol HA-1077 and Y-27632 30 μmol/l, Y-27632 30 μmol/l were cutured for 6 h. The number of SCC-4 cells treated with: HA-1077 (25, 50 and 100 μmol/l), HA-1077 50 μmol/l and/or Y-27632 30 μmol/l was significantly lower than control cells in BrdU assay [F (5.17) = 443.818, p<0.0001] and in KI-67 assay [F = 192.595, d.f. = 5,17; p<0.0001]. The results obtained suggest that the pathways that evolve ROCKs proteins play an important functional role in the positive regulation of cell proliferation in oral squamous cell carcinoma.